Analisis Rasio Likuiditas, Solvabilitas, Aktivitas, dan Profitabilitas Keuangan untuk Menilai Kinerja Keuangan PT. Unilever Indonesia Tbk yang Terdaftar di BEI Periode 2019-2023 - Safitri, Yesi; Firayanti, Yuni; Wulansari, Fidia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to determine the financial performance of PT. Unilever Indonesia Tbk for the period 2019-2023. The financial ratios used to measure financial performance are the Liquidity Ratio instrument Current Ratio, the Solvency Ratio measuring the instrument Debt Equity Ratio, the Activity Ratio measuring instrument Total Asset turnover, and the Profitability Ratio measuring instrument Profit Margin. The form of this research used is Qualitative. The place of the research is PT. Unilever Indonesia Tbk which is listed on the IDX. The subject of the research Financial report of PT. Unilever Indonesia Tbk for the period 2019-2023. The object of this research financial performance of PT. Unilever Indonesia Tbk for the period 2019-2023. The data collection technique for this research is documentation and literature study. The type of data used is secondary data. The data source of the financial report of PT. Unilever Indonesia Tbk for the period 2019-2023 is www.idx.co.id and www.unilever.co.id. The results of the research showed that the Liquidity Ratio was measured using the Current Ratio of PT. Unilever Indonesia Tbk's financial performance for the 2019-2023 period is less good result. The Solvency Ratio is measured using the Debt to debt-equity ratio of PT. Unilever Indonesia Tbk's financial performance for the 2019-2023 period is less good result. The Activity Ratio was measured using the Total Asset Turnover of PT. Unilever Indonesia Tbk's financial performance for the 2019-2023 period is good result. The Profitability Ratio is measured using the Net Profit Margin of PT. Unilever Indonesia Tbk's financial performance for the 2019-2023 period is less good result.